Postmortem analysis of the chemical compounds of aqueous humour obtained from the eye of European bison – preliminary results (European Bison Conservation Newsletter, 2015)
The aim of this study was the assessment of diagnostic utility of postmortem analysis of aqueous humour in lowland European bison. Samples of aqueous humour were collected from 12 male bison from Białowieża Forest during 24 hours after death. All animals were carefully sectioned and divided into two groups. The first group consisted of young animals from 3 months to 4 years old. Mature individuals 4–16 years old were included in the second group. During 48 hours after collection, all samples were analyzed with colorimetric method. The following parameters were determined: total calcium, ionized calcium, phosphorus, magnesium, sodium and potassium. The concentration of total calcium and ionized calcium as well as calcium/phosphorus and sodium/potassium ratios were higher in group of immature males comparing to fully mature individuals. In contrast, mature males had twofold higher phosphorus level than young animals. Similarly, concentration of magnesium, sodium and potassium were lower in animals belonging to the first group. Biochemical analysis of aqueous humour composition can be an useful diagnostic tool in cause of death determination, and appropriate interpretation of causes of pathological lesions found during necropsy. However, to make the results reliable, first reference values of various chemical compounds of aqueous humour in European bison should be established.
Keywords: European bison; eye; biochemistry; aqueous humour